FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KUALITAS TIDUR PADA REMAJA DI SMA PGRI 2 PADANG - Jumilia Jumilia (Ensiklopedia of Journal, 2020)
National Sleep Foundation found more than a third (36%) Teenagers reportedly have trouble sleeping, consequently teen activity is often found late in class due to sleep disturbances. Factors affecting sleep quality in adolescents include physiological, stress, behavioral, social and cultural, as well as environmental and lifestyle changes. The purpose of the research is to know Factors related to sleeps quality in adolescents at senior high school PGRI 2 Padang on 2019. This type of research is descriptive analytic with cross sectional study design, implemented in SMA PGRI 2 Padang in September 2019- February 2020. The population is all students with samples amounting to 61 people. The steps in data processing are editing, coding, entry and cleaning. Analysis of univariate data with frequency distribution and analysis of bivariate with test-square with confidence level 95%. The results of this study were obtained more half (65.6%) Teenagers with poor sleep quality, more than half (62.3%) Teenagers with moderate stress, more half (55.7%) Teenagers with less good environment, more half (55.7%) With an unkind lifestyle. In this study found a significant link between stress and sleep quality (p value = 0.000 value), Sleep-quality environment (p value = 0.000 value), sleep-quality lifestyle, (p value value = 0.001). Through head of SMA PGRI 2 Padang in order to involve parents in monitoring and supervising students ' sleep time to get a good quality of sleep. As well as monitoring and supervising students using gadgets in the school and effective learning activities (such as reducing assignments or homework) so that students get enough rest and sleep at home.